Carbon Nanodots as Functional Excipient to Develop Highly Stable and Smart PLGA Nanoparticles Useful in Cancer Theranostics - Nicolò Mauro; Mara Andrea Utzeri; Salvatore Emanuele Drago; Gianpiero Buscarino; Gennara Cavallaro; Gaetano Giammona (MDPI AG, 2020)
Theranostic systems have attracted considerable attention for their multifunctional approach to cancer. Among these, carbon nanodots (CDs) emerged as luminescent nanomaterials due to their exceptional chemical properties, synthetic ease, biocompatibility, and for their photothermal and fluorescent properties useful in cancer photothermal therapy. However, premature renal excretion due to the small size of these particles limits their biomedical application. To overcome these limitations, here, hybrid poly(lactic-co-glycolic acid) (PLGA-CDs) nanoparticles with suitable size distribution and stability have been developed. CDs were decisive in the preparation of polymeric nanoparticles, not only conferring them photothermal and fluorescent properties, needed in theranostics, but also having a strategic role in the stabilization of the system in aqueous media. In fact, CDs provide stable PLGA-based nanoparticles in aqueous media and sufficient cryoprotection in combination with 1% PVP. While PLGA nanoparticles required at least 5% of sucrose. Comparing nanosystems with different CDs content, it is also evident how these positively impinge on the loading and release of the drug, favoring high drug loading (~4.5%) and a sustained drug release over 48 h. The therapeutic and imaging potentials were finally confirmed through in vitro studies on a breast cancer cell line (MDA-MB-231) using fluorescence imaging and the MTS cell viability assay.